1997
DOI: 10.1111/j.1365-2133.1997.tb03673.x
|View full text |Cite
|
Sign up to set email alerts
|

A higher prevalence of onychomycosis in psoriatics compared with non-psoriatics: a multicentre study

Abstract: There is some controversy about the prevalence of onychomycosis in patients with psoriasis compared to non-psoriatics. We therefore measured the prevalence of toenail onychomycosis in psoriatics and non-psoriatics attending dermatologists' offices. None of the patients had a referring diagnosis of onychomycosis. The prevalence of pedal onychomycosis in psoriatics (n = 561) was 13%. The odds of patients with psoriasis having onychomycosis was 56% greater than non-psoriatics of the same age and sex (P = 0.02). I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

6
62
2
4

Year Published

2001
2001
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 126 publications
(74 citation statements)
references
References 19 publications
6
62
2
4
Order By: Relevance
“…In our study positive mycological cultures from nail specimens were obtained in 14 (20.8%) psoriatic patients. The prevalence of onychomycosis caused by yeasts in psoriatic patients is reported as 19-23 % [18,19]. Similarly to the previous report [16], in our study Candida albicans was the commonest isolated fungi in psoriatic patients with nail involvement.…”
Section: Discussionsupporting
confidence: 88%
“…In our study positive mycological cultures from nail specimens were obtained in 14 (20.8%) psoriatic patients. The prevalence of onychomycosis caused by yeasts in psoriatic patients is reported as 19-23 % [18,19]. Similarly to the previous report [16], in our study Candida albicans was the commonest isolated fungi in psoriatic patients with nail involvement.…”
Section: Discussionsupporting
confidence: 88%
“…[1][2][3] This disease is more common in older age groups and in selected populations, such as swimmers and individuals with diabetes mellitus or psoriasis. [4][5][6] Onychomycosis can be an infection reservoir for dermatomycoses of the adjacent skin, such as interdigital or plantar ("moccasin type") tinea pedis. Studies have shown that onychomycosis can have severe impact on quality of life, 7 and this disease should not be trivialized.…”
mentioning
confidence: 99%
“…Trichophyton rubrum ließ sich als der bedeutsamste Erreger feststellen [7]. Eine weitere wichtige Risikogruppe stellen Patienten mit Psoriasis dar: In einer Multicenterstudie fand sich eine Onychomykose der Füße bei 13% von 561 Psoriatikern, das Risiko wurde als 56% größer als bei Kontrollpersonen erachtet [16].…”
Section: Risikofaktorenunclassified